2021
DOI: 10.3390/ijms22105363
|View full text |Cite
|
Sign up to set email alerts
|

BPA, BPAF and TMBPF Alter Adipogenesis and Fat Accumulation in Human Mesenchymal Stem Cells, with Implications for Obesity

Abstract: Bisphenol A (BPA) is an endocrine-disrupting chemical used in the production of plastics, and is linked to developmental, reproductive, and metabolic disorders including obesity. Manufacturers have begun using ‘BPA-free’ alternatives instead of BPA in many consumer products. However, these alternatives have had much less testing and oversight, yet they are already being mass-produced and used across industries from plastics to food-contact coatings. Here, we used human female adipose-derived stem cells (hASCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 89 publications
2
23
0
Order By: Relevance
“…Hence, TMBPF is being marketed as a 'low toxicity' BPA replacement monomer. However, we and others have found that TMBPF does have toxic effects on human and rat stem cells, and other human cell lines, and at very low concentrations, calling into question the safety of this new chemical ( Cohen et al, 2021 , Harnett et al, 2021a , Harnett et al, 2021b , Szafran et al, 2017 ).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Hence, TMBPF is being marketed as a 'low toxicity' BPA replacement monomer. However, we and others have found that TMBPF does have toxic effects on human and rat stem cells, and other human cell lines, and at very low concentrations, calling into question the safety of this new chemical ( Cohen et al, 2021 , Harnett et al, 2021a , Harnett et al, 2021b , Szafran et al, 2017 ).…”
Section: Introductionmentioning
confidence: 91%
“…Similar to BPA, many of them are likely EDCs that interfere with hormone receptors and action. Numerous studies reveal the toxic potential of BPA analogs, showing various cellular, developmental, and reproductive disruptions across species ( Arancio et al, 2018 , Arancio et al, 2019 , Cohen et al, 2021 , Harnett et al, 2021a , Harnett et al, 2021b , Eladak et al, 2015 , Ge et al, 2014 , Huang et al, 2016 , Moreman et al, 2017 , Wang et al, 2017 , Wu et al, 2017 ). Importantly, studies in various animal models and cell systems report that some analogs such as BPAF, are even more toxic, potent, and estrogenic than the parent compound BPA ( Arancio et al, 2018 , Cohen et al, 2021 , Kojima et al, 2019 , Liang et al, 2017 , Michałowicz et al, 2015 , Moreman et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In summary, researchers can use the protocol described here to evaluate cytotoxicity during cell differentiation processes in vitro and for other applications, such as the study of the basic biology of stem cells or the screening of test substances that may interfere with adipogenesis [29] , [30] , [31] .…”
Section: Additional Informationmentioning
confidence: 99%
“…It was shown to not produce any estrogenic effects in both in vitro and in vivo [33,51]. According to a recent study, TMBPF has effects on adipogenesis and fat accumulation, having nonestrogenic, antiadipogenic effects [52]. Moreover, TMBPF revealed antiestro-genic and antiandrogenic activity in several cancer cell lines [33,53].…”
Section: Acceleration Of the Jnk And P38 Pathways By Tmbpf In Raw 2647 Cellsmentioning
confidence: 99%